Attitudes toward tobacco cessation and lung cancer screening in two South African communities. Issue 10 (2nd October 2020) - Hillyer, Grace C.; Mapanga, Witness; Jacobson, Judith S.; Graham, Anita; Mmoledi, Keletso; Makhutle, Raynolda; Osei-Fofie, Daniel; Mulowayi, Mubenga; Masuabi, Brenda; Bulman, William A.; Neugut, Alfred I.; Joffe, Maureen
ABSTRACT: Among men in South Africa, the prevalence of tobacco smoking is as high as 33%. Although smoking is responsible for most lung cancer in South Africa, occupational and environmental exposures contribute greatly to risk. We conducted a tobacco and lung cancer screening needs assessment and administered surveys to adults who smoked >100 cigarettes in their lifetime in Johannesburg (urban) and Kimberley (rural). We compared tobacco use, risk exposure, attitudes toward and knowledge of, and receptivity to cessation and screening, by site. Of 324 smokers, nearly 85% of current smokers had a <30 pack-year history of smoking; 58.7% had tried to stop smoking ≥1 time, and 78.9% wanted to quit. Kimberley smokers more often reported being advised by a healthcare provider to stop smoking (56.5% vs. 37.3%, p =0.001) than smokers in Johannesburg but smokers in Johannesburg were more willing to stop smoking if advised by their doctor (72.9% vs. 41.7%, p <0.001). Findings indicate that tobacco smokers in two geographic areas of South Africa are motivated to stop smoking but receive no healthcare support to do so. Developing high risk criteria for lung cancer screening and creating tobacco cessation infrastructure may reduce tobacco use and decrease lung cancer mortality in South Africa.